Chemokine profiles of interstitial pneumonia in patients with dermatomyositis: a case control study - Katsuhiro Oda (Nature Portfolio, 2017)
Abstract Chemokines play an important role in the pathophysiology of dermatomyositis (DM) with interstitial pneumonia (IP). However, the relation between chemokines and the disease activity or prognosis of DM-IP has not been elucidated. We evaluated the serum C-C motif chemokine ligand (CCL) 2, Th1 chemokines (C-X-C motif chemokine ligand [CXCL] 9, CXCL10, CXCL11), and Th2 chemokine (CCL17) profiles of 30 patients, and examined the relation between these chemokines and the disease activity or prognosis of DM-IP. Initial serum CCL2 level was higher in the death group (P = 0.007). To determine the cut-off points effective as poor prognostic factors of DM-IP, ROC curve analysis was carried out on initial serum CCL2 level. The value that maximized the area under the ROC curve was 894 pg/mL (sensitivity: 100%, specificity: 70.8%). Serum CCL2, CXCL9, CXCL10, and CXCL11 levels were lower at 2 weeks after treatment initiation than before treatment. Serum CCL2, CXCL10, and CXCL11 levels at 2 weeks after treatment initiation were higher in the death group. Serum levels of chemokines such as CCL2, CXCL10, and CXCL11 may be possible biomarkers of disease activity and prognosis in DM-IP, and serum CCL2 level may be useful when deciding initial treatment.